Pyelonephritogenic Diffusely Adhering Escherichia coli EC7372 Harboring Dr-II Adhesin Carries Classical Uropathogenic Virulence Genes and Promotes Cell Lysis and Apoptosis in Polarized Epithelial Caco-2/TC7 Cells - Guignot, Julie (American Society for Microbiology, 2000)
Diffusely adhering Escherichia coli (DAEC) strains expressing adhesins of the Afa/Dr family bind to epithelial cells in a diffuse adherence pattern by recognizing a common receptor, the decay-accelerating factor (CD55). Recently, a novel CD55-binding adhesin, named Dr-II, was identified from the pyelonephritogenic strain EC7372. In this report, we show that despite the low level of sequence identity between Dr-II and other members of the Afa/Dr family, EC7372 induces pathophysiological effects similar to those induced by other Afa/Dr DAEC strains on the polarized epithelial cell line Caco-2/TC7. Specifically, the Dr-II adhesin was sufficient to promote CD55 and CD66e clustering around adhering bacteria and apical cytoskeleton rearrangements. Unlike other Afa/Dr DAEC strains, EC7372 expresses a functional hemolysin that promotes a rapid cellular lysis. In addition, cell death by apoptosis or necrosis was observed in EC7372-infected Caco-2/TC7 cells, depending on infection time. Our results indicate that EC7372 harbors a pathogenicity island (PAI) similar to the one described for the pyelonephritogenic strain CFT073, which carries both hly and pap operons. Cumulatively, our findings indicate that strain EC7372 can be considered a prototype of a subclass of Afa/Dr DAEC isolates that have acquired a PAI harboring several classical uropathogenic virulence genes.